1977
DOI: 10.1068/p060615
|View full text |Cite
|
Sign up to set email alerts
|

Müller-Lyer Illusions: Their Origin in Processes Facilitating Object Recognition

Abstract: Perspective theories for the Muller-Lyer illusions have considered them to reflect constancies normally permitting the viewer to compensate for distance in estimating the true size of three-dimensional objects. Our experiments suggest a rather different perspective theory involving object recognition.A novel experimental procedure was used. Each of the separate groups of thirty subjects viewed only one of nineteen experimental drawings based on the Muller-Lyer figures. They judged the overall length of the sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
4

Year Published

1981
1981
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 11 publications
2
53
4
Order By: Relevance
“…A systematic reduction in apparent expansion was found with the successiveremoval of the wings in the wingsout figure: The decreases in the apparent extent of the shaft-present wings-out figure were 3.04, 4.54, and 6.34 mm when two wings, three wings, and four wings, respectively, were amputated. In contrast, for the wings-in figure, previous investigators have found no decrease in underestimation with removal of two wings (Warren & Bashford, 1977) or a decrease that is dependent upon the placement of the remaining wings (Day & Dickinson, 1976a). Furthermore, a decrease in illusory magnitude has been reported for the removal of three wings, yet the degraded figure was still significantly underestimated (Day & Dickinson, 1976a;Warren & Bashford, 1977).…”
Section: Discussionmentioning
confidence: 43%
See 3 more Smart Citations
“…A systematic reduction in apparent expansion was found with the successiveremoval of the wings in the wingsout figure: The decreases in the apparent extent of the shaft-present wings-out figure were 3.04, 4.54, and 6.34 mm when two wings, three wings, and four wings, respectively, were amputated. In contrast, for the wings-in figure, previous investigators have found no decrease in underestimation with removal of two wings (Warren & Bashford, 1977) or a decrease that is dependent upon the placement of the remaining wings (Day & Dickinson, 1976a). Furthermore, a decrease in illusory magnitude has been reported for the removal of three wings, yet the degraded figure was still significantly underestimated (Day & Dickinson, 1976a;Warren & Bashford, 1977).…”
Section: Discussionmentioning
confidence: 43%
“…Support for a dual-illusion hypothesis is suggested by the differential changes in illusory magnitude that were observed for the Mueller-Lyer wings-in and wings-out figures with systematic wing amputation in the first study and in previous studies (e.g., Day & Dickinson, 1976a;Warren & Bashford, 1977). A systematic reduction in apparent expansion was found with the successiveremoval of the wings in the wingsout figure: The decreases in the apparent extent of the shaft-present wings-out figure were 3.04, 4.54, and 6.34 mm when two wings, three wings, and four wings, respectively, were amputated.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…According to Greist-Bousquet and Schiffman (1985), although wings-out overestimation is greater than the wings-in underestimation for conventional full-line Miiller-Lyer figures, the reverse applies for the amputated Muller-Lyer figures. Specifically, as indicated by the results of Greist-Bousquet and Schiffman (1981c) and Warren and Bashford (1977), amputated wings-in MullerThanks are extended to Peter Wende roth for his comments on a draft of this paper, and to two anonymous reviewers for their helpful critical reviews of themanuscript. Correspondence should be addressed to lohn Predebon, Department of Psychology, University of Sydney, Sydney, NSW 2006, Australia. …”
mentioning
confidence: 99%